2022
DOI: 10.1002/jsfa.11834
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile, secondary compounds and antioxidant activities in the fresh forage, hay and silage of sainfoin (Onobrychis viciifolia) and sulla (Hedysarum coronarium)

Abstract: Background: Sainfoin (Onobrychis viciifolia) and sulla (Hedysarum coronarium) are forage legumes usually preserved to optimize their utilization as feedstuffs. However, the method of preservation modifies the chemical composition differently in both legume species. Secondary compounds (such as proanthocyanidins, fatty acids, carotenoids and tocopherols) present in forages affect the quality of animal products. Therefore, the effect of preservation on the contents of secondary compounds should be investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Meanwhile, SH, compared to both FSF and DSF, was characterized by higher fiber components and lower levels in protein, energy, vitamin E, phenolic compounds, and ALA; these differences can be attributed to either the more advanced development stage of the harvested forage, or consistent nutrient loss occurred during the hay-making process. In addition, Rufino-Moya et al [ 42 ] observed an analogous reduction in vitamin E and ALA due to the hay-making of sulla forage, whereas only a slight decrease was recorded in polyphenols and antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, SH, compared to both FSF and DSF, was characterized by higher fiber components and lower levels in protein, energy, vitamin E, phenolic compounds, and ALA; these differences can be attributed to either the more advanced development stage of the harvested forage, or consistent nutrient loss occurred during the hay-making process. In addition, Rufino-Moya et al [ 42 ] observed an analogous reduction in vitamin E and ALA due to the hay-making of sulla forage, whereas only a slight decrease was recorded in polyphenols and antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…Fievez et al demonstrated that increased productions of anteiso -BCFA were linked to increased amylolytic populations. Moreover, although PACs have inhibitory effects on microbial growth and on proteolysis, reducing ruminal concentrations of BCFA, we suggest that the low PAC content in the sainfoin concentrates compared with that in fresh sainfoin , due to the pelleting process could not be enough to justify the changes in BCFA ruminal concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the FA profile of concentrates, plasma, and meat samples was performed at the CITA (Spain). The FA profile of the concentrates was analyzed using 500 mg of lyophilized samples following the method described by Rufino-Moya et al 12 For plasma and meat FA profiles, 2 mL and 500 mg of lyophilized samples, respectively, were extracted according to Lee et al 18 Afterward, all the samples were methylated as FA methyl esters using 4 mL of 0.5 M CH 3 ONa/CH 3 OH solution followed by 4 mL of acetyl chloride/CH 3 OH (1:10, v:v) and extracted in 3 mL of heptane. After, the FA concentration was determined in a Bruker Scion 436-GC gas chromatograph (Bruker, Billerica, MA, USA) with a flame ionization detector equipped with a CP-8400 autosampler and an SP-2560 capillary column (100 m × 0.25 mm ID × 0.20 μm for concentrate samples and 200 m × 0.25 mm ID × 0.20 μm for plasma and meat samples; Sigma-Aldrich, Saint Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fatty acid (FA) profile of the freeze-dried seeds was determined in a Bruker Scion 436 gas chromatograph with flame ionisation detector (Bruker, Billerica, MA, USA) equipped with a CP-8400 autosampler and an SP-2560 capillary column (100 m × 0.25 mm × 0.2 µm) (Supelco, Saint Louis, MO, USA) according to Rufino-Moya et al (2022) [7]. Briefly, 1 µL was injected with a split relation 1:125 at 280 • C; the oven temperature was set at 125 • C for 15 min and reached 190 • C at 90 min at 5 • C/min.…”
Section: Determination Of Lipid Content and Fatty Acids Profilementioning
confidence: 99%